2009
DOI: 10.1111/j.1471-4159.2009.06315.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor properties of human mesencephalic neural progenitor cells: NMDA enhances dopaminergic neurogenesis in vitro

Abstract: Human midbrain‐derived neural progenitor cells (NPCs) may serve as a continuous source of dopaminergic neurons for the development of novel regenerative therapies in Parkinson’s disease. However, the molecular and functional characteristics of glutamate receptors in human NPCs are largely unknown. Here, we show that differentiated human mesencepahlic NPCs display a distinct pattern of glutamate receptors. In whole‐cell patch‐clamp recordings, l‐glutamate and NMDA elicited currents in 93% of NPCs after 3 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Data from several groups have suggested that neural stem cells and neural progenitors may express low levels of the NMDA receptor [25,26]. We tested the expression of all known NMDAR subunits in wt ST14A cells by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Data from several groups have suggested that neural stem cells and neural progenitors may express low levels of the NMDA receptor [25,26]. We tested the expression of all known NMDAR subunits in wt ST14A cells by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Ca 2+ transients in differentiated hCBiPSCs rose in a less pronounced fashion and in a fewer percentage of cells (22%) when glutamate receptors were stimulated, compared to studies with differentiated human fetal NPCs (>95%) [80]. On the other hand, during application of GABA more cells (62%) responded with higher Ca 2+ amplitudes in comparison with differentiated fetal NPCs (48%) [81].…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitter-driven proliferation has been observed in the embryonic and adult brains of vertebrates (Schlett, 2006;Borta and Hoglinger, 2007;O'Keeffe et al, 2009;Wegner et al, 2009;Jhaveri et al, 2010;Rodrigo et al, 2010), and multiple reports hint that these small peptides also influence proliferation within the postembryonic retina of chickens, frogs, fish, and salamanders [reviewed in (Martins and Pearson, 2008)]. For example, glucagon, derived from amacrine cells, suppresses CMZ cell proliferation (Fischer et al, 2005) while serotonin, secreted by photoreceptors and found in the aqueous humor, promotes CMZ cell proliferation (De Lucchini et al, 2003;Reisoli et al, 2008).…”
Section: Neurotransmitters and Neuronal Activitymentioning
confidence: 98%